Answer:
The required Prove is shown below.
Step-by-step explanation:
Consider the provided proof.
The angle addition postulate states that if C is in the interior of AOB , then
m∠AOC+m∠COB=m∠AOB
Transitive property of equality: If a = b and b = c, then a = c.
Substitution property: If x = y, then one can replace x with y.
Commutative property of addition: a + b = b + a
Now use above property to prove m∠EBA = m∠CBD
Statement: Reason:
m∠1 = m∠3 Given
m∠EBA = m∠2 + m∠3 Angle Addition Postulate
m∠EBA = m∠2 + m∠1 Substitution Property of Equal
m∠EBA = m∠1 + m∠2 Commutative Property of Addition
m∠1 + m∠2 = m∠CBD Angle Addition Postulate
m∠EBA = m∠CBD Transitive Property of Equality
Hence, the required Prove is shown above.